Egyptian Private Higher Education at a Crossroads - Levy, Daniel; Sabry, Manar (International Higher Education, 2011)
The Egyptian Revolution comes amid a period of national and general regional growth of private higher education. Indeed, the Middle East is the last region to establish the private sector across the breadth of its countries. Apart from a few precursors such as the American University in Cairo, the private sector is basically a creation of the last two decades, and its share in Egypt is still small, though it is growing. On the one hand, the new minister says private universities should be distinctive, not "duplicating" public ones and thus offering new programs: on the other hand regulations about access cannot be ruled out nor can caps on the amount of tuition rises. Already evident is a public policy orientation to discourage for-profit private higher education.